ARE EXERCISE-BASED INTERVENTIONS EFFECTIVE IN REDUCING INJURIES IN TACKLE COLLISION BALL SPORTS? A SYSTEMATIC REVIEW. Issue 4 (1st February 2017) - Sewry, Nicola; Verhagen, Evert; Lambert, Mike; van Mechelen, Willem; Viljoen, Wayne; Readhead, Clint; Brown, James
Abstract : Background: The injury burden in rugby union is relatively high compared to other team sports. Therefore rugby would benefit by having effective injury prevention programmes. Exercise-based interventions have successfully reduced injuries in soccer studies, but evidence on exercise-based interventions in tackle collision sports, such as rugby, is limited. Objective: To systematically examine the evidence of exercise-based intervention programmes reducing injuries in tackle collision sports. Design: Systematic review. Setting: PubMed, EbscoHost and Web of Science were searched for articles published between January 1995 and December 2015. The methodological quality was assessed using an adapted Cochrane Bone Joint and Muscle Trauma Group quality assessment tool. Patients (or Participants): N/A as this is a systematic review abstract. Interventions (or Assessment of Risk Factors): The inclusion criteria were: 1) all types of randomised controlled trials and cohort studies 2) sporting codes: American, Australian and Gaelic football, rugby union and rugby league 3) participants of any age or sex 4) exercise-based, prehabilitative intervention, and 5) primary outcome was injury number or incidence. The exclusion criteria were: 1) full-text of the article was unavailable 2) the article was unavailable in English. Main Outcome Measurements: Effectiveness, and injury number or incidence. Results: Nine studies with a total of 3517 participants were included in this review. Seven studies showed a statistically significant decrease in their primary outcome (injuries). These studies included three different sporting codes and various age groups, making it difficult to be confident about the inferences. The two studies that had the highest methodological quality showed no statistically significant decrease in injury incidence following an exercise-based intervention. Conclusions: There is a lack of consistent evidence from high-level studies that exercise-based interventions in tackle collision sports reduce injuries.